NEUTROPHIL-LYMPHOCYTE RATIO AND ITS ASSOCIATION WITH GLYCEMIC CONTROL AMONG TYPE-2 DIABETES MELLITUS PATIENTS IN A TERTIARY CARE HOSPITAL, CHENGALPATTU DISTRICT - KARTHIK SIGAMANI; SHIMI SUNDER RAJA KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Neutrophil-lymphocyte ratio (NLR) is a novel marker of sub-clinical inflammation which is associated with the worsening of insulin resistance in type-2 diabetes mellitus (type-2 DM) patients. Plasma glycated hemoglobin (HbA1c) is a major investigatory tool for monitoring long-term glycemic control. The objective of this study was to find out the relationship between NLR and HbA1c levels in patients with type-2 DM. Methods: This was a cross-sectional study carried out in the central clinical laboratory of a tertiary care hospital. Complete blood count and HbA1c laboratory reports of all type-2 DM patients were retrieved from the registers. NLR was calculated by dividing the absolute neutrophil count (ANC) by the absolute lymphocyte count. The patients were categorized into three groups based on the HbA1c values. Data were tabulated and analyzed using the Statistical Package for the Social Sciences v 23.0. Results: The mean age of the total 143 patients was 49 years with a slight male preponderance (52.4%). The mean NLR was 2.76 and the mean HbA1c value was 8.18%. A statistically significant association was found between HbA1c with NLR (p<0.001), ANC (p<0.001), and age of the patients (p<0.001). Conclusion: NLR is a simple and cost-effective diagnostic test that can be used as a marker of sub-clinical inflammation and also predict the development of cardiovascular complications in type-2 diabetic patients with poor glycemic control.